THE INFLUENCE OF SERVICE QUALITY DIMENSIONS ON CUSTOMER SATISFACTION IN LIMITED COMPANIES (PT). ADIRA DINAMIKA MULTI FINANCE SATELLITE SIDENRENG RAPPANG DISTRICT - Kadir, Abdul (Jurnal Manajemen Dan Bisnis, 2023)
This research aims to assess the influence of service quality dimensions, namely Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), and Tangibles (X5), on customer satisfaction (Y) in the Limited Liability Company (PT) Adira Dinamika Multi Finance Satellite Sidenreng Rappang. Through the distribution of questionnaires to 65 respondents, the study found that all service quality dimensions both partially and simultaneously affect customer satisfaction. Service quality emphasizes meeting customer needs and delivering services accurately as per expectations. The correlation analysis results indicate that the Reliability dimension (X1) has the most dominant influence on customer satisfaction, reaching 86.8%, while 13.2% is influenced by other factors not investigated in this study. The F-test confirms that collectively, service quality dimensions significantly influence customer satisfaction. With an F-value of 85.194, far exceeding the F-table (2.37), the research supports that these variables have a significant simultaneous impact. The second hypothesis, stating that the Reliability dimension (X1) has a dominant influence, is substantiated with the highest t-value of 6.429 and a significance of 0.000. Therefore, H0 is rejected, and Ha is accepted. In this series of findings, it can be concluded that the Reliability dimension is the key factor in enhancing customer satisfaction at PT Adira Dinamika Multi Finance in Sidenreng Rappang.